2006
DOI: 10.1002/pmic.200500920
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive quantitative proteome analysis of 20S proteasome subtypes from rat liver by isotope coded affinity tag and 2-D gel-based approaches

Abstract: Quantitative protein profiling is an essential part of proteomics and requires technologies that accurately, reproducibly, and comprehensively identify and quantify proteins. Over the past years, many quantitative proteomic methods have been developed. Here, 20S proteasome subtypes isolated from rat were compared by four approaches based on the combination of isotope-coded affinity tag (ICAT), 2-DE, LC and ESI and MALDI MS: (i) 2-DE, (ii) ICAT/2-DE MALDI-MS, (iii) ICAT/LC-ESI-MS, (iv) ICAT/LC-MALDI-MS. A defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Furthermore, the subunits of these proteasomes were separated by 2D gel electrophoresis and the protein spots from proteasome purified from the brain and spleen were identified by mass spectrometry. All spots between 20 and 30 kDa were matched to proteasomal subunits, indicating the purity of the preparations, and altogether, 14 subunits were identified in chicken as already found in humans, mice, and rats (Claverol et al 2002;Froment et al 2005;Schmidt et al 2006). Actually, the number of excised spots exceeded that of the proteasome subunits by 4, indicating that some proteins might be post-translationally modified, e.g., by glycosylation, phosphorylation, acetylation, or deamination and therefore have different properties, e.g., a different isoelectric point.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the subunits of these proteasomes were separated by 2D gel electrophoresis and the protein spots from proteasome purified from the brain and spleen were identified by mass spectrometry. All spots between 20 and 30 kDa were matched to proteasomal subunits, indicating the purity of the preparations, and altogether, 14 subunits were identified in chicken as already found in humans, mice, and rats (Claverol et al 2002;Froment et al 2005;Schmidt et al 2006). Actually, the number of excised spots exceeded that of the proteasome subunits by 4, indicating that some proteins might be post-translationally modified, e.g., by glycosylation, phosphorylation, acetylation, or deamination and therefore have different properties, e.g., a different isoelectric point.…”
Section: Discussionmentioning
confidence: 56%
“…By means of 2D PAGE of 20S proteasomes, we had previously shown that liver contains proteasomes exclusively of an intermediate-type subunit composition, i.e., they contain standard as well as immuno-subunits (Schmidt et al 2006). Applying the same technique, we analysed the subunit composition of the three proteasome subpopulations of young and aged rats, respectively, and assigned the proteasome subunits according to our earlier investigations ( Fig.…”
Section: Separation Of 20s Proteasome Into Subpopulationsmentioning
confidence: 99%
“…Applying the same technique, we analysed the subunit composition of the three proteasome subpopulations of young and aged rats, respectively, and assigned the proteasome subunits according to our earlier investigations ( Fig. 3a) (Schmidt et al 2006). Relative quantification of the active site containing subunits β1 and β1i as well as of β5 and β5i was performed by using subunits α2 and β4 as reference spots.…”
Section: Separation Of 20s Proteasome Into Subpopulationsmentioning
confidence: 99%
See 2 more Smart Citations